2005
DOI: 10.1115/1.1835363
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Decorin and Biglycan on Mechanical Properties of Multiple Tendons in Knockout Mice

Abstract: Evaluations of tendon mechanical behavior based on biochemical and structural arrangement have implications for designing tendon specific treatment modalities or replacement strategies. In addition to the well studied type I collagen, other important constituents of tendon are the small proteoglycans (PGs). PGs have been shown to vary in concentration within differently loaded areas of tendon, implicating them in specific tendon function. This study measured the mechanical properties of multiple tendon tissues… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
146
3

Year Published

2006
2006
2009
2009

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 168 publications
(161 citation statements)
references
References 50 publications
12
146
3
Order By: Relevance
“…Together, the PG changes in this overstrained tensile tendon may negatively impact the structural integrity and mechanical properties of the tendon and potentially predispose to rupture. Reduced levels of small leucine-rich PGs would be expected to affect collagen fibrillogenesis and fibril mechanical properties as well as increase the susceptibility of the collagen fibers to cleavage by collagenolytic MMPs (47)(48)(49).…”
Section: Discussionmentioning
confidence: 99%
“…Together, the PG changes in this overstrained tensile tendon may negatively impact the structural integrity and mechanical properties of the tendon and potentially predispose to rupture. Reduced levels of small leucine-rich PGs would be expected to affect collagen fibrillogenesis and fibril mechanical properties as well as increase the susceptibility of the collagen fibers to cleavage by collagenolytic MMPs (47)(48)(49).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, it was believed that absence of decorin would lead to weaker tissues and that the opposite trend could be expected if decorin is overexpressed. However, either superior or similar material parameters have recently been reported for tendons from decorin deficient adult [37] and postnatal mice [34] as well as decorin deficient engineered gels [16], compared to wild-type controls. In addition, greater than normal decorin expression has been reported in prolapsed mitral valve [38] in which the tissue is weakened [39], and our lab has histochemically demonstrated that excess decorin is present valves that were exposed to altered shear stress [40].…”
Section: Discussionmentioning
confidence: 99%
“…Various investigators have assessed the contributions of selected matrix components (e.g., cytokines, proteoglycans) to tendon structure, composition, and mechanical properties using transgenic and knockout mice. [14][15][16][17][18][19][20][21][22] Despite the importance of these findings, the alteration or removal of matrix proteins may result in an abnormal or pathologic tissue phenotype due to biological compensation. 16 Therefore, these animal models may be inappropriate for studying the genetic regulation of normal tendon and ligament properties.…”
Section: Introductionmentioning
confidence: 99%